PERPUSTAKAAN KOLABORATIF (MAKERSPACE LIBRARY) DI BANJARBARU - Bilah, Muhammad El'Arif; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
The library in Banjarbaru is still considered as nothing more than a place to read books and the books themselves are only old book collections, this creates a stigma that libraries do not develop according to the needs of people who are too dependent on digitalization and technology. This is the underlying reason why people lack interest in visiting the library. Therefore, it is necessary to develop a library as a new face of public space that can accommodate activities for collaboration and offer social networks for the Banjarbaru community. The purpose of designing a Collaborative Library (Makerspace Library) in Banjarbaru is to create an educated, accustomed to reading, and highly cultured community. Through the library, people can exchange information and knowledge.